Ranitidine bismuth citrate: A review - N Chiba; RH Hunt; ABR Thomson (Canadian Journal of Gastroenterology)
Recognition of the relationship between Helicobacter pylori infection and the development of gastroduodenal disease has increased greatly in recent years. To avoid complications of H pylori infection, such as the development of recurrent duodenal and gastric ulcers, effective therapies are required for eradication of the infection. This article reviews ranitidine bismuth citrate (RBC), a novel complex of ranitidine, bismuth and citrate, which was developed specifically for the purpose of eradicating H pylori. Dual therapy with RBC in combination with clarithromycin for 14 days yields eradication rates of 76%. Triple therapy bid for one week with a proton pump inhibitor, clarithromycin and either amoxicillin or a nitroimidazole (tinidazole or metronidazole) is advocated as the treatment of choice for H pylori eradication. Analogous regimens with RBC in place of proton pump inhibitors show effective eradication rates in comparative studies and with pooled data. RBC, used alone or in combination with other antibiotics, appears to be a safe and effective drug for the treatment of H pylori infection. Bismuth levels do not appear to rise to toxic levels.